ANGPTL8: An Important Regulator in Metabolic Disorders - Luo, Mengdie; Peng, Daoquan (Frontiers in Endocrinology, 2018)
Long-term controversy regarding the role of angiopoietin-like protein 8 (ANGPTL8) in beta-cell proliferation and diabetes progression made it a research spotlight. Recently the controversy was resolved. Although ANGPTL8 could not control beta-cell expansion and islet function, ANGPTL8 was still considered as a novel but atypical member in the ANGPTL family because of its unique structure and crucial effects on lipid metabolism. Besides, ANGPTL8 also participated in some other disorders such as non-alcoholic fatty liver disease and renal dysfunction. Understanding the features of ANGPTL8 may offer new diagnostic and therapeutic approaches to metabolic-related diseases. Therefore, we reviewed most recent findings about ANGPTL8 and aimed to provide an integrated picture of ANGPTL8.